Contribution of V(H) replacement products in mouse antibody repertoire. - Lin Huang; Miles D Lange; Yangsheng Yu; Song Li; Kaihong Su; Zhixin Zhang (PLoS ONE, 2013)
VH replacement occurs through RAG-mediated recombination between the cryptic recombination signal sequence (cRSS) near the 3' end of a rearranged VH gene and the 23-bp RSS from an upstream unrearranged VH gene. Due to the location of the cRSS, VH replacement leaves a short stretch of nucleotides from the previously rearranged VH gene at the newly formed V-D junction, which can be used as a marker to identify VH replacement products. To determine the contribution of VH replacement products to mouse antibody repertoire, we developed a Java-based VH Replacement Footprint Analyzer (VHRFA) program and analyzed 17,179 mouse IgH gene sequences from the NCBI database to identify VH replacement products. The overall frequency of VH replacement products in these IgH genes is 5.29% based on the identification of pentameric VH replacement footprints at their V-D junctions. The identified VH replacement products are distributed similarly in IgH genes using most families of VH genes, although different families of VH genes are used differentially. The frequencies of VH replacement products are significantly elevated in IgH genes derived from several strains of autoimmune prone mice and in IgH genes encoding autoantibodies. Moreover, the identified VH replacement footprints in IgH genes from autoimmune prone mice or IgH genes encoding autoantibodies preferentially encode positively charged amino acids. These results revealed a significant contribution of VH replacement products to the diversification of antibody repertoire and potentially, to the generation of autoantibodies in mice.